La- and Mn-doped cobalt spinel oxygen evolution catalyst for proton exchange membrane electrolysis - Chong, Lina; Gao, Guoping; Wen, Jianguo; Li, Haixia; Xu, Haiping; Green, Zach; Sugar, Joshua D; Kropf, A Jeremy; Xu, Wenqian; Lin, Xiao-Min; Xu, Hui; Wang, Lin-Wang; et al. (Science (American Association for the Advancement of Science), 2023)
Discovery of earth-abundant electrocatalysts to replace iridium for the oxygen evolution reaction (OER) in a proton exchange membrane water electrolyzer (PEMWE) represents a critical step in reducing the cost for green hydrogen production. We report a nanofibrous cobalt spinel catalyst codoped with lanthanum (La) and manganese (Mn) prepared from a zeolitic imidazolate framework embedded in electrospun polymer fiber. The catalyst demonstrated a low overpotential of 353 millivolts at 10 milliamperes per square centimeter and a low degradation for OER over 360 hours in acidic electrolyte. A PEMWE containing this catalyst at the anode demonstrated a current density of 2000 milliamperes per square centimeter at 2.47 volts (Nafion 115 membrane) or 4000 milliamperes per square centimeter at 3.00 volts (Nafion 212 membrane) and low degradation in an accelerated stress test.